1996
DOI: 10.1038/bjc.1996.133
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-S-transferase activity and isoenzyme levels measured by two methods in ovarian cancer, and their value as markers of disease outcome

Abstract: Summary A study has been carried out to investigate the cellular distribution and levels of glutathione-Stransferase isoenzymes (GST), acidic (7t), basic (x) and neutral (p), in ovarian tumour biopsies, and to measure GST activity in the same tumour specimens. Two methods of assessing isoenzyme levels (immunohistochemistry and Western blot) were compared. Well-known important clinicopathological features were correlated with response to treatment, overall survival and progression-free survival for each of 97 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Early studies carried out in breast cancer patients failed to establish a correlation between GST expression and clinicopathological features such as disease-free and overall survival [34,35]. Confirming these results, no association was found between the expression of any of the GSTs analysed and response to treatment, overall survival and disease-free survival in ovarian cancer [36]. However, a more recent analysis found that patients homozygous for a GST A1 polymorphism that results in reduced expression of the enzyme showed a significant difference in 5-year survival after breast cancer treatment when compared to heterozygous patients [37]; indeed, low expression of GST A1 correlated with reduced risk of death in the 5 years following diagnosis.…”
Section: Discussionsupporting
confidence: 69%
“…Early studies carried out in breast cancer patients failed to establish a correlation between GST expression and clinicopathological features such as disease-free and overall survival [34,35]. Confirming these results, no association was found between the expression of any of the GSTs analysed and response to treatment, overall survival and disease-free survival in ovarian cancer [36]. However, a more recent analysis found that patients homozygous for a GST A1 polymorphism that results in reduced expression of the enzyme showed a significant difference in 5-year survival after breast cancer treatment when compared to heterozygous patients [37]; indeed, low expression of GST A1 correlated with reduced risk of death in the 5 years following diagnosis.…”
Section: Discussionsupporting
confidence: 69%
“…These conflicting results might be explained by differences in techniques used to quantify GSTP1-1 (Table 3). It has been shown that immunohistochemical quantification of GSTP1-1 did not always correlate with the concentrations of GSTP1-1 as measured in the tissue cells by other methods, such as Western blot analysis (9,14). Wrigley et al (14) concluded that the Western blotting technique was more sensitive than immunohistochemistry because it detected GSTP1-1 that had been missed by observer examination of stained sections.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that immunohistochemical quantification of GSTP1-1 did not always correlate with the concentrations of GSTP1-1 as measured in the tissue cells by other methods, such as Western blot analysis (9,14). Wrigley et al (14) concluded that the Western blotting technique was more sensitive than immunohistochemistry because it detected GSTP1-1 that had been missed by observer examination of stained sections. In addition, different scoring systems to quantify GSTP1-1 by immunohistochemistry, observer variation in identifying positively stained cells, different cutoff points for discriminating high from low values, and different types of tissue, i.e., fresh versus formalin fixed and paraffin embedded may also be responsible for the conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, proliferative rate [9,12,15,[17][18][19][20][21][22][23][24] , growth factors and their receptors [25] , lamina receptors [26] and functional and structural alterations of oncogenes and oncosuppressor genes [21,22,[25][26][27][28][29] have been studied. Biomarkers directly involved in drug resistance, such as proteins associated with multidrug resistance detoxification [30][31][32][33][34][35][36] , have also been determined as indicators of clinical outcome. However, due to the marked biologic, pathologic, and clinical tumor heterogeneity, outcome and interpretation of translational studies are often not equivocal.…”
mentioning
confidence: 99%